Pengaruh Kualitas Layanan Petugas Agen Brilink (PAB) Terhadap Loyalitas Agen Brilink - Marpaung, Jenny Emile Paulina; Suharjo, Budi; Asnawi, Yudha Heryawan (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
This study aims to analyze the effect of the service quality of BRILink Agent Officers (PAB) on the level of satisfaction, trust and loyalty of BRILink Agents in order to achieve the BRILink Agent transaction volume target. This study used a questionnaire with a five-point Likert scale. Questionnaires were submitted to 300 respondents, namely BRILink agents who were used as samples, which were located in West Jakarta, Banten and West Kalimantan. Respondent requirements are BRILink Agents who have been BRI Agents for a minimum of 6 months and the number of transactions is under 200 transactions per month. Questionnaires were distributed by BRI employees, namely the Resident Auditor Unit (RAU) in the local area. There were 274 questionnaires that were returned and were completely filled out. The data analysis technique uses the Structural Equation Model (SEM) method and uses Lisrel 8.72 software to analyze the casual relationship between service quality, satisfaction, trust and loyalty of BRILink agents, and to evaluate hypotheses regarding the relationship between model construction. The results of this study indicate that all Service Quality indicators have a significant effect on BRIink Agent Satisfaction, BRILink Agent Satisfaction has a significant effect on BRILink Agent Trust and Loyalty. What greatly affects the satisfaction, trust and loyalty of BRILink Agents is the frequency of PAB visits to BRILink Agents, PAB's ability to motivate BRILink Agents, and BRI must improve the quality of the system and network. Keywords: loyalty, service quality, satisfaction, trust, SEM